Postoperative nursing of a patient with cervical spondylotic myelopathy (1例脊髓型颈椎病患者的术后护理体会) - TIAN Yixian (田忆贤); WANG Ting (王婷); HU Yiyuan (胡译元); LI Jiaqi (李佳琪); XUE Ning (薛宁); SONG Xiaofei (宋晓菲); LI Zeyu (李泽宇); LI Fan (李帆); ZOU Fang (邹芳) (Association of Integrative Nursing, 2023)
This paper summarized the postoperative nursing measures for a patient with cervical spondylotic myelopathy. Based on the postoperative nursing assessment, interventions such as pain control, gastrointestinal function care, airway management were carried out. Traditional Chinese Medicine nursing techniques including intradermal needling, auricular acupoint pressing, Chinese herbal medicine hot-compress, external application and fumigation were conducted under the guidance of syndrome differentiation. The nursing of integrated traditional Chinese and western medicine is effective to relieve the pain, improve the gastrointestinal function and prevent the postoperative complications. (本文总结1例脊髓型颈椎病患者术后护理经验。基于术后护理评估, 实施疼痛干预、胃肠道功能干预、呼吸系统管理等护理措施。在常规护理的基础上, 通过辨证施护, 开展皮内针、耳穴压丸、中药热奄包、药膏涂擦及熏蒸等中医适宜护理技术。中西医结合护理干预能够有效减轻患者疼痛, 改善胃肠道功能, 预防并发症。)